Growth, yield, and yield related characteristics of sweet corn hybrids organically grown in a tropical highland - Ladiasmi, Uci; Chozin, Mohammad; Fahrurrozi, Fahrurrozi; Sudjatmiko, Sigit (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2025)
The development of organic sweet corn varieties is ideally addressed to have a good adaptation to a variety of environmental conditions. This study aims to evaluate the performance of 17 sweet corn hybrids, consisting of 15 promising hybrids and 2 commercial hybrids grown organically in the highlands. The study was conducted in Batu City, East Java (1160 m above sea level) and arranged in a completely randomized block design with three replications. Evaluation was carried out on growth performance, productivity, and yield quality. The findings of the study showed that all tested hybrids exhibited good growth performance, as indicated by robust plant and a lot of leave. Nevertheless, Caps 2 x Caps 22, Caps 5 x Caps 17B, Caps 17B x Caps 23, and Caps 22 x Caps 23, respectively, emerged as the best hybrids in terms of overall growth performance. In terms of the productivity and quality of the ears produced, the hybrids Caps 5 x Caps 17B, Caps 5 x Caps 22, Caps 15 x Caps 17A, Caps 17A x Caps 17B, and Caps 17B x Caps 22 demonstrated their superiority in ear yields while meeting all established market quality standards.These findings suggest that, for orgnic production, these five hybrids can serve as the alternative for commercial varieties adressed for conventional production. Further evaluation on the yield stability across environmental conditions is needed to make these hybrids more predictable and dependable for the organic growers.